Digital Technology inclusion in the math teaching in pandemic context: an intern’s case - Fernanda Renzulli; Patricia Noemi Cavatorta; Camila Barzan (Espacios en Blanco. Serie Indagaciones)
In the year 2020, the abrupt closure of the educational institutions because of the covid-19 pandemic, provoked a forced mutation to the long distance education. The classrooms and the teaching proposals needed to be reinvented to fulfill the demands of the moment in the isolation context.